Indigenous Community Projects: Addressing Colonization through Using Culture as a Protective Factor - Gordon, Heather Sauyaq Jean; Zukowski, Amy (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2023)
Indigenous communities have painful histories of colonization, resulting in historical trauma and adverse current community conditions (CCCs). This is a mixed method study of Administration for Native Americans grants that includes analysis of project summaries and CCCs as well as a analysis of impact and effectiveness scores finished projects are given by ANA evaluators. The results show that all grants included in the analysis are addressing colonization and almost half of the grants are utilizing culture as a protective factor. The projects using culture as a protective factor have significantly higher effectiveness ratings, which means they are achieving their objectives more than those not using culture. Grantee project examples are in the discussion. The paper concludes with policy implications for funders.